Use of cross-sectoral data linkage to predict high-rate offenders in Western Australia - Ferrante, Anna; Randall, Sean; Boyd, James; Tubex, Hilde; Morgan, Frank (International Journal of Population Data Science, 2018)
Introduction Studies have repeatedly found that a small number of offenders account for a disproportionate amount of crime. High-rate, persistent offenders (so-called ‘prolific’ offenders) have a major impact on local crime rates and public perceptions of safety, and place a substantial financial and social burden on communities. Objectives and Approach Using population-level administrative data, our study identifies ‘prolific’ offenders in WA and describes their demographic and crime profiles. The official criminal records of all offenders born in WA between 1980 and 1995 were linked to administrative records from health, education and child protection databases (followed to 2005). Linked data on families (parents and siblings) were also included. Using this information, the study identified factors that distinguish between prolific and non-prolific offenders. The study also examined whether correlates of prolific offending were similar between a) male and female offenders, and b) Indigenous and non-Indigenous offenders. Results Clusters of offenders exhibiting a high-rate and persistent pattern of offending over the life-course were identified. These ‘prolific’ offenders accounted for a disproportionate amount of crime and criminal justice contacts: 8% of female offenders accounted for 41% of female contacts; 3% of male offenders made up 21% of male contacts; 9% of Indigenous offenders made up 37% of Indigenous contacts; 7% of non-Indigenous offenders made up 36% of non-Indigenous contacts. Being the subject of a maltreatment allegation, being placed in out-of-home care, and having a serious mental health condition before the age of 18 increased the odds of being a prolific offender. Two criminogenic factors - early onset of offending (contact before age 12) and early violence - emerged as the most significant predictors. Conclusion/Implications Child protection and mental health services have much of the information needed to target early prevention, while criminal justice agencies are well-placed to apply crime reduction strategies through the targeting of early-onset/early-violent offenders. A combined approach is likely to have the greatest effect on reducing impact of prolific offending.